Antiproliferative Activity of Philippine Marine Sediment-Derived Actinomycetes - Maglonzo, Jon Ray M; Sabido, Edna M; Salibay, Cristina C; Dalisay, Doralyn S; Saludes, Jonel P (UI Scholars Hub, 2022)
The Philippine archipelago is rich in marine biodiversity and resources that are widely unexplored. Its marine sediments harbor marine microbes that possess secondary metabolites with potent bioactivities. This study aims to determine the antiproliferative activity of the crude extracts of selected Actinomycete isolates (DSD011, DSD017, and DSD042) from Islas de Gigantes, Carles, Iloilo. The antiproliferative screening was done using Saccharomyces cerevisiae as a model organism. Crude extracts of isolates that are active in inhibiting the growth of S. cerevisiae were determined using the broth microdilution method. Afterward, the active extract was tested using antiproliferative and budding yeast assays. With the antiproliferative model, only DSD011 was found to inhibit the growth of S. cerevisiae. The percentage of live and dead cells in DSD011 was comparable to those treated with Triton X (positive control). Further, the budding yeast analysis showed that DSD011 induced G1 cell cycle arrest of nearly 50% of S. cerevisiae cells. Thus, DSD011, a marine sediment-derived Actinomycete, serves as a potential source of naturally occurring bioactive compounds with antiproliferative properties.